Alkaline industrial wastes – Characteristics, environmental risks, and potential for mine waste management. (15th April 2023) - Moyo, Annah; Parbhakar-Fox, Anita; Meffre, Sebastien; Cooke, David R.
Abstract: The large quantities of alkaline industrial wastes that are generated globally have the potential to be valorized in various applications instead of being landfilled. This study evaluated the potential reuse of green liquor dregs (GLD), wood ashes, coal ash, red mud, mussel, scallop, and oyster shells to control acid and metalliferous drainage (AMD). Low hydraulic conductivities (10 −7 to 10 −9 m/min) suggest that covers constructed from fine-grained GLD, red mud, coal ash and wood fly ash can limit the formation of AMD. Static and kinetic test leachates of pH 5.8 to 10.6 indicate that the tested materials can neutralize acidic drainage and immobilize metal(loid)s by precipitation. The alkalinity is proportional to the amount and reactivity of carbonate and hydroxide fractions with red mud followed by coal ash being the most alkaline over 100 weeks and wood ashes the least. The tested industrial wastes generate leachates with a low metal(loid) risk when screened against the Australian freshwater guidelines. However, oxyanions including Al, Cr, Cu, Se, and V were leached in deleterious concentrations ≤100 times more than the guidelines because of their mobility in alkaline conditions. The outcomes of this study highlighted that alkaline industrial wastes can be potentially used in the long-term remediation of AMD as part of an environmentally sustainable and cost-effective integrated mine waste management strategy. Graphical abstract: Image 1 Highlights: Limitation of AMD formation by materials with low permeability and high compaction. Details long-term acid-neutralization and metal mitigation by alkaline wastes. Relates alkalinity of waste to amount and reactivity of carbonates and hydroxides. Evaluates low metal risk in alkaline leachates and high concentration of oxyanions. Offers opportunities for value recovery of alkaline wastes and remediation of AMD.